2003
DOI: 10.1002/evan.10108
|View full text |Cite
|
Sign up to set email alerts
|

On stony ground: Lithic technology, human evolution, and the emergence of culture

Abstract: Culture is the central concept of anthropology. Its centrality comes from the fact that all branches of the discipline use it, that it is in a way a shorthand for what makes humans unique, and therefore defines anthropology as a separate discipline. In recent years the major contributions to an evolutionary approach to culture have come either from primatologists mapping the range of behaviors, among chimpanzees in particular, that can be referred to as cultural or “proto‐cultural” 1, 2 or from evolutionary th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(101 citation statements)
references
References 35 publications
0
100
0
1
Order By: Relevance
“…I feel confident that we will eventually find that the basal differences between the human clade and that of our closest living relatives are no greater than those between, say, chimpanzees and bonobos, and that ''the gap between humans and chimpanzees, between a few termites for lunch and Beethoven, is filled with incremental steps.'' 128 As we learn more, we can expect this to prove true of other, higher taxa as well.…”
Section: Resultsmentioning
confidence: 94%
“…I feel confident that we will eventually find that the basal differences between the human clade and that of our closest living relatives are no greater than those between, say, chimpanzees and bonobos, and that ''the gap between humans and chimpanzees, between a few termites for lunch and Beethoven, is filled with incremental steps.'' 128 As we learn more, we can expect this to prove true of other, higher taxa as well.…”
Section: Resultsmentioning
confidence: 94%
“…This forms an essential step towards examining fine-scale geographic variation in the behavior and morphology of Pleistocene African hominin populations that included early representatives of Homo sapiens (cf. Clark, 2002;Foley and Lahr, 2003). Accomplishing this goal requires data at finely resolved spatial and temporal scales and an understanding of the causes, behavioral or otherwise, that define archaeological variation.…”
Section: Discussionmentioning
confidence: 99%
“…The enlargement of the parietal areas is a discrete and well-expressed trait of the endocranium of H. sapiens (Bruner et al, 2003(Bruner et al, , 2011Bruner, 2004;Neubauer et al, 2009Neubauer et al, , 2010Gunz et al, 2010). Considering the role of the parietal areas in the perception and management of the relationships between inner and outer world (Bruner, 2010a), a two-part model of the evolution of modern humans might also explain some of the differences between early (Middle Stone Age/Middle Paleolithic) and late (Later Stone Age/ Upper Paleolithic) modern human cultures (Klein, 2000(Klein, , 2008Foley and Lahr, 2003;Wynn and Coolidge, 2003;Coolidge and Wynn, 2005). It has been long suggested that morphological and behavioral modernity could have been decoupled along the evolution of H. sapiens and that 'modernity' evolved not as a single package but as a combination of characters evolved in different times and places (Stringer, 2006(Stringer, , 2007Tattersall, 2009).…”
Section: Phylogeny and Evolutionmentioning
confidence: 99%